Distribution of Carbapenemase Genes among Carbapenem-Non-Susceptible Acinetobacter baumanii Blood Isolates in Indonesia: A Multicenter Study - Dewi Anggraini; Dewi Santosaningsih; Yulia Rosa Saharman; Pepy Dwi Endraswari; Cahyarini Cahyarini; Leli Saptawati; Zinatul Hayati; Helmia Farida; Cherry Siregar; Munawaroh Pasaribu; Heriyannis Homenta; Enty Tjoa; et al. (MDPI AG, 2022)
Carbapenem non-susceptible Acinetobacter baumannii (CNSAB) is an important pathogen that causes nosocomial bacteremia among critically ill patients worldwide. The magnitude of antibiotic resistance of A. baumanii in Indonesia is expected to be significant; however, the data available are limited. The aim of this study was to analyze the genetic profiles of CNSAB isolates from patients with bacteremia in Indonesia. CNSAB isolates from blood cultures of bacteremia patients in 12 hospitals in Indonesia were included. The blood cultures were conducted using the BacT/Alert or BACTEC automated system. The CNSAB were identified with either Vitek 2 system or Phoenix platform followed by a confirmation test using a multiplex polymerase chain reaction (PCR) assay, targeting the specific gyrB gene. The carbapenemase genes were detected by multiplex PCR. In total, 110 CNSAB isolates were collected and were mostly resistant to nearly all antibiotic classes. The majority of CNSAB isolates were susceptible to tigecycline and trimethoprim-sulfamethoxazole (TMP-SMX), 45.5% and 38.2%, respectively. The blaOXA-51-like gene was identified in all CNSAB isolates. Out of the total, 83.6% of CNSAB isolates had blaOXA-23-like gene, 37.3% blaOXA-24-like gene, 4.5% blaNDM-1 gene, 0.9% blaIMP-1 gene, and 0.9% blaVIM gene. No blaOXA-48-like gene was identified. The blaOXA-23-like gene was the predominant gene in all except two hospitals. The presence of the blaOXA-24-like gene was associated with resistance to tigecycline, amikacin, TMP-SMX and cefoperazone-sulbactam, while blaOXA-23-like gene was associated with resistance to TMP-SMX and cefoperazone-sulbactam. In conclusion, the blaOXA-23-like gene was the predominant gene among CNSAB isolates throughout Indonesia. A continuous national surveillance system needs to be established to further monitor the genetic profiles of CNSAB in Indonesia.